A Phase 1/2 Randomized, Placebo-Controlled Trial of Romidespin in Persons With HIV-1 on Suppressive Antiretroviral Therapy. (21st December 2020) - McMahon, Deborah K; Zheng, Lu; Cyktor, Joshua C; Aga, Evgenia; Macatangay, Bernard J; Godfrey, Catherine; Para, Michael; Mitsuyasu, Ronald T; Hesselgesser, Joseph; Dragavon, Joan; Dobrowolski, Curtis; Karn, Jonathan; et al.
Abstract: Background: Romidepsin (RMD) is a histone deacetylase inhibitor reported to reverse HIV-1 latency. We sought to identify doses of RMD that were safe and induced HIV-1 expression. Methods: Enrollees had HIV-1 RNA <40 copies/mL on antiretroviral therapy. Measurements included RMD levels, plasma viremia by single-copy HIV-1 RNA assay, HIV-1 DNA, cell-associated unspliced HIV-1 RNA (CA-RNA), acetylation of histone H3-lysine-9 (H3K9ac + ), and phosphorylation of transcription factor P-TEFb. Wilcoxon tests were used for comparison. Results: In the single-dose cohorts 1–3, 43 participants enrolled (36 participants 0.5, 2, 5 mg/m 2 RMD; 7 placebo) and 16 enrolled in the multidose cohort 4 (13 participants 5 mg/m 2 RMD; 3 placebo). One grade 3 event (neutropenia) was possibly treatment related. No significant changes in viremia were observed in cohorts 1–4 compared to placebo. In cohort 4, pharmacodynamic effects of RMD were reduced proportions of CD4 + T cells 24 hours after infusions 2–4 (median, −3.5% to −4.5%) vs placebo (median, 0.5% to 1%; P ≤ .022), and increased H3K9ac + and phosphorylated P-TEFb in CD4 + T cells vs placebo ( P ≤ .02). Conclusions: RMD infusions were safe but did not increase plasma viremia or unspliced CA-RNA despite pharmacodynamic effects on CD4 + T cells. Clinical Trials Registration: NCT01933594. Abstract : The histone deacetylase inhibitor, romidepsin, failed to induce HIV expression when administered to persons with HIV on suppressive ART. Expected pharmacodynamic effects of romidepsin were observed but did not lead to significant changes in plasma viremia or unspliced cell-associated RNA.